Call Management in High Performance Outbound Interactive Voice Response Management System - (:unkn) unknown (IEEE, 2016)
Organizations need to announce activities (e.g meetings), run polls, give information, gather feedback about their business and make advertisements. With the improvements in IVR technology, fixed & mobile phones create a great opportunity to meet those needs. Mass-IVR System was designed with those facts and necessities as motive and it provides the ability to call millions of telecom subscribers, let them listen a designated voice message and collect their feedbacks in the form of Dual Tone Multi-Frequency (DTMF) codes. In this paper tools and techniques for call management in high performance outbound interactive voice response management system is explained.
Keywords: IVR; Mass Calls; DTMF; Announcement; Optimization